Evaluation of catastrophic health expenditure risk due to measles in Nigeria - Ryoko Sato (Taylor & Francis Group, 2022)
Measles can have a substantial negative impact not only on people's health but also on their finances, especially in developing countries. This study evaluates the household risk of catastrophic health expenditure (CHE) due to measles, according to regions and wealth quintiles. The CHE risk due to measles was computed based on (1) the likelihood of health service utilization to treat measles, (2) out-of-pocket (OOP) expenditure and indirect costs associated with disease treatment, and (3) household consumption expenditures. I derived the CHE risk associated with measles, conditional on contracting the disease, across regions and wealth quintiles in Nigeria, using secondary data sources for health-care utilization, OOP expenditures, and consumption expenditures. There was a large variation in CHE risk according to regions and wealth quintiles. Among the poorest households, those in the northeast and northwest would have the highest risk of CHE, up to 17%, while those in the southwest would have the lowest risk of 5%. For all regions, as the wealth increases, the CHE risk would decrease. There would be zero or very little CHE risk among the richest households in any regions. Given the proven efficacy of measles vaccines, immunizations can prevent households, especially poorer households in northeast and northwest regions, from facing the CHE risk due to measles.